Work Like Ants! Atta 2.0: Dealing with Self-Organized Teams - Ecar, Miguel; da Silva, João Pablo Silva (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2021: Anais do XVII Simpósio Brasileiro de Sistemas de Informação, 2021)
Traditional software engineering approaches were developed based on the old manufacturing process, in term of roles, responsibilities, tasks and hierarchy. Modern approaches, such as, Agile approaches, are based on a fusion of these traditional approaches and the Agile Manifesto, which changes the perspective of main software process objectives. These approaches are designed to encourage self-management, which may be challenging even in big or very small software companies. This paper proposes a software engineering complementary framework called Atta Plug-in 2.0 (Atta 2), that is an approach inspired by a nature organization and aims to deal with the difficulties of self-organization issues. We performed a case study on a start-up company, that follows Scrum guidelines, has a very small team and maintain several projects at the same time. As the outcome, we have a successfully running the Atta 2 and obtained gains in term of self-organization, structure and visibility. Based on this we advocate that Atta 2 improved Sprint planning and execution, tasks creation and distribution and slightly the quality of delivered artefacts. We also focus that Atta 2 helped to integrate new team members and to extract the best from the new ones and old team members. We advocate that Atta 2, may have value to the community, once it is a complementary option to aggregates value to well known agile or traditional approaches. Thus, we concluded that Atta 2 can be used jointly with other management approaches, in order to promote the best-aggregated value.